PENGEMBANGAN MEDIA FLASHCARD BERBASIS DIGITAL PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI HAK DAN KEWAJIBAN SISWA KELAS III SEKOLAH DASAR KABUPATEN LIMA PULUH KOTA - Rahmadini, Fitria; Reinita; Waldi, Atri; Safitri, Serly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the suboptimal use of digital learning media in Pancasila Education lessons on Rights and Obligations in third grade elementary school. Based on observations and interviews, teachers still predominantly use conventional media in the form of pictures in books and classroom displays, resulting in less varied learning and suboptimal student engagement. This study aims to produce valid, practical, and effective digital flashcard media. The type of research used was Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The data collection instruments were validation sheets (material, language, and media) and questionnaires for teachers and students. The research subjects consisted of 14 third-grade students from UPTD SDN 05 VII Koto Talago (trial), 15 third-grade students from UPTD SDN 06 VII Koto Talago (implementation), and 9 third-grade students from UPTD SDN 09 VII Koto Talago (dissemination). The results of the study show that the developed media obtained a validity score of 94.34% in the highly valid category. Practicality, based on the responses of teachers and students, was in the highly practical category with a percentage ranging from 87.5% to 95.83%. The effectiveness of the media was demonstrated through improved learning outcomes with completion rates of 90.71%, 96%, and 91.11%, as well as an N-Gain calculation in the moderate category. Thus, digital flashcard media is declared valid, practical, and effective for use in teaching Pancasila in third grade elementary school.